1997
DOI: 10.1097/00006534-199704000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Surface Laser Scanning to Measure Facial Movement

Abstract: Linear and area measurements on the surface contour of the face have been recorded in a variety of chosen facial postures using surface laser scanning techniques on healthy volunteers. Subjects were scanned before and after active and voluntary (against resistance) movements. Quantitative measurements of changes in these lengths and areas were made by computer integration to provide an impression of the changes that accompany facial expression. Lip movements were found to be associated with dimensional changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 4 publications
0
12
1
1
Order By: Relevance
“…This four-dimensional process can be recorded by modern scanning procedures such as those already employed in cardiology for analyzing the beating heart [22]. A primary drawback of this 4-D procedure is, however, its relatively high imprecision [4,17] and high cost. That is why many authors employ video-based procedures [1,11,19,20,[23][24][25][26] that also represent facial structures twodimensionally.…”
Section: Diskussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This four-dimensional process can be recorded by modern scanning procedures such as those already employed in cardiology for analyzing the beating heart [22]. A primary drawback of this 4-D procedure is, however, its relatively high imprecision [4,17] and high cost. That is why many authors employ video-based procedures [1,11,19,20,[23][24][25][26] that also represent facial structures twodimensionally.…”
Section: Diskussionmentioning
confidence: 99%
“…Dieser vierdimensionale Vorgang kann durch moderne Scanverfahren, wie sie beispielsweise im Bereich der Kardiologie zur Analyse des schlagenden Herzens bereits im Einsatz sind [22], erfasst werden. Ein Hauptnachteil dieser 4-D-Verfahren liegt jedoch in ihrer relativ hohen Ungenauigkeit [4,17] und ihrem hohen Anschaffungspreis. Aus diesen Gründen verwenden viele Autoren videobasierte Verfahren [1,11,19,20,[23][24][25][26], welche die fazialen Strukturen ebenfalls zweidimensional abbilden.…”
Section: Diskussionunclassified
“…The texture and radiometric value of the CCD images may be added to the 3D data to obtain a realistic surface model of the object. Additional information on the system for medical application can be found in Bush and Antonyshyn (1996), Cacou et al. (1997), Yamada et al.…”
Section: Structured Light: Triangulationmentioning
confidence: 99%
“…For the stereo photogrammetry technique, Ferrario et al. (1999) applied 2 mm reflective markers and Cacou et al. (1997) applied 5 mm diameter blue vellum paper spots on the landmarks.…”
Section: Design Of Pre‐signalised Targetsmentioning
confidence: 99%
“…In children, differences between left and right sides were noted and were particularly evident in the middle and lower parts of the face, 26 but there is no agreement about this observation. 10,11,19 Throughout our study, we found that adults were much more symmetric and repetitive in the direction of their movements than children.…”
Section: Discussionmentioning
confidence: 51%